Mobilising Nepalese Missions for Tourism Promotion - Bhattarai, Chandra Prasad (NCWA Annual Journal, 2024)
With a huge comparative advantage, the tourism sector is Nepal’s most potential sector for its economic development. Despite this, it has not yet been established as the engine of economic growth. The immense opportunities for its development can contribute eventually to the overall development of the country. The slow pace in its international marketing is one of the reasons behind the weak performance of the industry. Nepal’s diplomatic missions can be mobilized effectively for branding and marketing if the government has a proper strategy for this. The Ministry of Tourism should realize this first, and take initiatives in benefitting from Nepal’s diplomatic presence in the major source markets worldwide.